Terson Syndrome: A Rare, Treatable Visual Loss After Subarachnoid and Intraventricular Hemorrhage: Poster Presentation - Case Report - Resident - DITA PERMATASARI; SYNTIA NUSANTI; MUHAMMAD SIDIK; SALMAREZKA DEWIPUTRI; SITA PARAMITA AYUNINGTYAS (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Intracranial pathologies commonly affect vision through optic neuropathy. However, visual loss could be due to vitreous hemorrhage as in Terson syndrome. This report warns us rare cases of visual loss after intracranial hemorrhage that requires totally different management than more commonly found optic neuropathies. Case Illustration : Female, 46 years old, had a severe headache and decreased consciousness two days later. CT angiography revealed wide subarachnoid hemorrhage and intraventricular hemorrhage causing hydrocephalus. She received emergency lumbar drainage followed by digital subtraction angiography and flow diverter device. Postoperative she regained consciousness, CT scan showed reduced ventricular size without residual hemorrhage, yet visual acuity of left eye reduced to hand movement and did not improve until one month later. Ophthalmologic examination showed vitreous hemorrhage of the left eye. Right eye was normal. Vitrectomy was planned to clear the vitreous hemorrhage. Discussion : Terson syndrome is intraocular hemorrhage associated with subarachnoid hemorrhage, cerebral hemorrhage, or traumatic brain injury. The proposed mechanisms were transmission of subarachnoid blood to the optic nerve sheath and rapid effusion of cerebrospinal fluid into the optic nerve sheath due to sudden increase of intracranial pressure. It compresses central retinal vein, causing vascular rupture. The manifestations could be vitreous, subhyaloid, subretinal, or intraretinal hemorrhage. Visual prognosis is good in those resolved spontaneously or receiving vitrectomy in nonresolving cases. Conclusion : Visual loss from intracranial hemorrhage or trauma could be caused by intraocular hemorrhage. It deserved different management than optic neuropathies. Prompt recognition should improve the management and the prognosis of rare cases such as Terson syndrome.